2019
DOI: 10.1103/physrevd.99.115016
|View full text |Cite
|
Sign up to set email alerts
|

Origin of a two-loop neutrino mass from SU(5) grand unification

Abstract: In this work we propose a renormalizable model based on the SU (5) gauge group where neutrino mass originates at the two-loop level without extending the fermionic content of the Standard Model (SM). Unlike the conventional SU (5) models, in this proposed scenario, neutrino mass is intertwined with the charged fermion masses. In addition to correctly reproducing the SM charged fermion masses and mixings, neutrino mass is generated at the quantum level, hence naturally explains the smallness of neutrino masses.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…Hence, we find only two models for genuine radiative neutrino masses in minimal scalar extensions of renormalizable SU (5). Both possibilities have been considered in the literature and it has been shown that they allow for successful unification [22,23]. Extending both the scalar and the fermionic sectors leads to the remaining six models.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hence, we find only two models for genuine radiative neutrino masses in minimal scalar extensions of renormalizable SU (5). Both possibilities have been considered in the literature and it has been shown that they allow for successful unification [22,23]. Extending both the scalar and the fermionic sectors leads to the remaining six models.…”
Section: Discussionmentioning
confidence: 99%
“…This leads to neutrino masses at the two-loop level. Viable solutions for neutrino masses and unification in the SU (5)-completion of S8 have been pointed out previously [23]. There are eight different ways to embed minimal radiative neutrino mass models with an additional fermion into SU (5).…”
Section: Model Scalar Contentmentioning
confidence: 95%
See 2 more Smart Citations
“…The neutrino mass matrix elements, again, are 20) where m i , i = 1, 2, 3, are neutrino mass eigenstates and U PMNS represents Pontecorvo-Maki-Nakagawa-Sakata (PMNS) unitary mixing matrix. Since we work in the basis where Y d is diagonal and real the unitary matrix that diagonalizes the neutrino matrix must be identified with the PMNS matrix.…”
Section: )mentioning
confidence: 99%